Relationship between Parent-Adolescent Interaction and the likelihood of Internalizing and Externalizing Problems Among Adolescents - Majid, Betty Nadhroh Ummah; Widyasari, Dian Caesaria; Karmiyati, Diah; Syakarofath, Nandy Agustin (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Adolescence is a transition phase from childhood to adulthood characterized by many drastic changes that make them vulnerable to internalizing and externalizing problems. However, parents can guide in managing the crisis by establishing warm, meaningful, and open interactions with adolescents. Therefore, this study examines the relationship between parent-adolescent interactions on the likelihood of experiencing internalizing and externalizing problems. This quantitative correlational study involved 180 participants from six Junior High Schools in East Java, selected through simple random sampling. Two instruments used were the Parent-Child Interaction Questionnaire-Revised Child Version (PACHIQ-R CH) and the Strenght and Difficulties Questionnaire (SDQ). Simple linear regression analysis indicated a significant effect of parent-adolescent interaction on internalizing and externalizing problems. It is suggested that parent-adolescent interactions contribute to the likelihood of adolescents experiencing internalizing and externalizing problems. Building warm, meaningful, and open interactions with adolescents assume to assist them in understanding the adaptive way of expressing emotions and overcoming the drastic changes during the transitional period.